(3QSGdI aj GdELeGYs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B... (3GYde Cf GdQShd Udi Gddg Ydjg hSde deG HYK ddQSGdI aHdZ eG CfRd Gddg Edjg aj eOI KdGK hYTQjf SfI GfJTQ cKjQ ef CMcGeg Hjf GdCeI hUGQJ ef GdGfJTGQ cGdTeS aj hSW GdfgGQ (B...s
(3BNQgG (B:s
.. (3hjLhR GdGNJdGaGJ aj JMbjb GdELeGY GdeQcH hef jYJbO GdMb dG jNQL Yf Gdbhdjf hef dG jYJbO jNQL hcPdc MGd GdRGFO Ydi Gdbhdjf aj LejY eG PcQJ hGddg gh GdYGde HMbGFb GdCMcGe (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 49s
(3GdPQjYI (B6\1455s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs